Teacher’s Enforcing Positive Interdependence: Students’ Perceptions - Siti Mina Tamah (Widya Mandala Surabaya Catholic University, 2012)
As there is a tendency to regard that a classroom without the label of ‘cooperative learning’ is not a good one, recent instructional practices then often utilize group work to encourage students to gain knowledge from one another – to assist and to seek assistance from their peers in addition to from the classroom teacher. Classrooms have the typical characteristics of small groups. The lock-step mode of instruction has been implicitly discouraged. Group seating in classrooms requires a teacher to keep into consideration the essential components of cooperative learning. One of the two critical components most widely reviewed is Positive Interdependence. With the trend to incorporate cooperative learning in the classroom practices, this Positive Interdependence is undoubtedly to be imposed to obtain the beneficial outcomes of cooperative efforts. Simply put, how can a teacher actively engage their students in their group work? How can a teacher enforce Positive Interdependence when implementing group work? This paper provides a model of enforcing students who are accustomed to having a non-cooperative learning class. It is in fact an attempt of the writer to share her classroom practice – what she has done to make the students really work as a group. To be more particular, this paper is intended to reveal students’ perceptions on the writer’s attempt to enforce the cooperative learning component – Positive Interdependence.